Fathers' Involvement in the Developmental Care of Their Preterm Newborns and its Impact on the Bonding and Self-Efficacy: A Nonrandomized Clinical Trial - Jila Mirlashari; Liisa Holsti; Hadi Ranjbar; Mahnaz Sanjari; Fatemeh Morovati; Zahra Daneshvar Ameri (Mashhad University of Medical Sciences, 2021)
Background: Premature birth and postpartum hospitalization can hurt the father-newborn bonding and self-efficacy.Aim: This study aimed to investigate the effect of fathers' involvement in premature newborns care on paternal-infant bonding and self-efficacy.Method: This nonrandomized clinical trial was conducted on 80 fathers of hospitalized newborns in the Neonatal Intensive Care Unit at Arash Hospital, Tehran University of Medical Sciences, Tehran, Iran, 2017. The samples were selected by the convenience sampling method and divided into two groups. Pre- and post-intervention outcomes were collected using the Parent-Infant Bonding Scale (originally the Mother-Infant Bonding Scale) and the Perceived Maternal Parenting Self-Efficacy tool. The gathered data were analyzed using independent t-test, paired t-test, repeated-measures ANOVA.Results: The mean±SD of the scores of the bonding score was reduced by 2.3±2.17 in the Control group and 5.27±2. 57 in the intervention group. A lower score represented a better bonding. The self-efficacy score increased in both groups; however, it was significantly higher in the intervention group, which was increased by 8.85±5.046, compared to 1.27±3.31 in the Control group.Implications for Practice: Developmental care by fathers can improve the father-infant bonding and increase the paternal self-efficacy for the care of the high-risk newborn.